Contrasting Trends of Religious Markets in Contemporary Mainland China and in Taiwan - Zhai, Jiexia Elisa (A journal of church and state, 2010)
During the past half-century, both China and Taiwan have experienced dramatic social and political change. Taiwan's economy has grown dramatically and has becom